Retrospective analysis of 217 fatal intoxication autopsy cases from 2009 to 2021: temporal trends in fatal intoxication at Tongji center for medicolegal expertise, Hubei, China - Lihua, Lin; Yuning, Wang; Henghui, He; Xiang, Liu; Min, Jiang; Zehao, Li; Lianjie, Li; Qian, Liu (Frontiers in Public Health, 2023)
This retrospective analysis of fatal poisoning case autopsies was performed at Tongji Center for Medicolegal Expertise in Hubei (TCMEH) from 2009 to 2021 to obtain up-to-date information on poisoning cases. The objective was to describe important data about evolving patterns in poisoning occurrences, enhance public safety policies, and assist forensic examiners and police in handling such cases more effectively. Analyses based on sex, age, topical exposure routes, toxic agents, and mode of death were carried out using 217 records of poisoning cases collected from TCMEH as a sample, and the results were compared with reports previously published (from 1999 to 2008) from this institution. Deaths from poisoning occurred at a higher rate in males than females and were most common among individuals aged between 30 and 39 years. The most frequent method of exposure was oral ingestion. The causative agents of deadly poisoning have changed when compared to the data from the previous 10 years. For instance, whereas deaths from amphetamine and drug overdoses are gradually becoming more prevalent, deaths due to carbon monoxide and rodenticide poisonings have declined dramatically. In 72 cases, pesticides continued to be the most frequent poisoning cause. A total of 60.4% of the deaths were accidental. Men died from accidents at a higher rate than women, although women were more likely to commit suicide. Particular focus is needed on the use of succinylcholine, cyanide, and paraquat in homicides.